Degradable dry-state water-absorbing fabric based on pre-swelling as well as preparation method and application of degradable dry-state water-absorbing fabric

Through the pre-swellable, degradable dry water-absorbing fabric preparation method, the problem of poor mechanical properties of hydrogel dressings when stress concentration is solved, forming a fibrous hydrogel with good water absorption and mechanical properties, suitable for complex or chronic wounds treatment.

CN119465617APending Publication Date: 2025-02-18SOUTH CHINA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411529206.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing hydrogel dressings have poor mechanical properties when stress concentration and simple stimulation responsiveness, and cannot effectively simulate the nanofiber filamentous structure of the skin extracellular matrix, limiting their application in complex or chronic wound treatment.

Method used

Using the pre-swellable degradable dry water-absorbing fabric preparation method, the base cloth is soaked in a pre-swelling solution and heated, followed by alkalizing treatment with microwave assistance, and added chloroacetic acid solution for etherification to form good water-absorbing. and mechanical properties of fibrous hydrogels.

Benefits of technology

The prepared dry water-absorbing fabric forms a fibrous hydrogel with good liquid retention ability and transparency after rapidly absorbing liquid. It is suitable for various wound repair scenarios, overcomes the lack of mechanical properties and stimulation response of traditional hydrogel dressings. The problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465617A_ABST
    Figure CN119465617A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of medical materials, and discloses a degradable dry-state water-absorbing fabric based on pre-swelling as well as a preparation method and application of the degradable dry-state water-absorbing fabric. The preparation method comprises the following steps: firstly, carrying out pre-swelling treatment on base cloth by using a salt solution, an ionic liquid or a surfactant solution; then carrying out alkalization treatment on the base cloth by adopting a microwave-assisted technology; then carrying out etherification treatment; and drying to obtain the degradable dry-state water-absorbing fabric. The fiber structure is effectively promoted to expand by pre-treating the base cloth. The preparation process of the dry-state water-absorbing fabric is simple and controllable, and large-scale production is easy to realize; after absorbing liquid, the obtained dry-state water-absorbing fabric can form fibrous hydrogel with good liquid retention capacity and transparency, is suitable for various wound repair scenes, and has wide market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical materials, and particularly relates to a pre-swelling-based degradable dry water-absorbent fabric and a preparation method and application thereof. Background Art

[0002] Wound dressings are an integral part of wound management. Their role is not only to protect wounds from infection, but also to provide a suitable environment to promote wound healing. With the development of medical technology, traditional dressings can no longer meet the needs of modern wound treatment, especially when dealing with complex or chronic wounds.

[0003] Hydrogel wound dressings play an increasingly important role in modern wound care due to their unique moisture retention and biocompatibility. Early hydrogel dressings were mainly used to absorb wound exudate and provide basic physical protection. With the understanding of the moist healing environment, hydrogel dressings began to integrate more bioactive ingredients, such as growth factors and antibacterial agents. Modern hydrogel dressings can not only promote wound healing, but also have intelligent responsiveness and can adjust drug release according to changes in the wound environment.

[0004] With the innovation of materials science and the increasing public attention to the concept of sustainable development, hydrogel dressings have shown a significant trend of diversification in material selection. This includes not only traditional synthetic polymers such as polyacrylic acid and polyethylene glycol, but also polymers of natural origin, such as hyaluronic acid and collagen. In addition, semi-synthetic polymers, including quaternized chitosan and carboxymethyl cellulose, have also been added to the material library of hydrogel dressings, broadening the range of raw materials. The application of preparation technologies such as dynamic chemical bonding, photocross-linking in situ polymerization, double networks, semi-interpenetrating networks, and 3D printing has improved the performance and functionality of hydrogel dressings. In addition, hydrogel dressings are also developing in the direction of functional integration. Multifunctional integrated hydrogel dressings combine multiple functions, such as antibacterial, healing promotion, intelligent response, etc., and can provide comprehensive treatment solutions, which is the future development direction of hydrogel dressings.

[0005] As a new type of dressing, hydrogel has gradually become a hot topic in wound dressing research due to its advantages such as moisture retention, biocompatibility, and biodegradability. However, hydrogel cannot overcome stress concentration and exhibits poor mechanical properties and simple stimulus responsiveness. In addition, unlike the nanofibrous filamentous structure of the skin extracellular matrix (ECM), hydrogels mostly present a honeycomb mesh structure and cannot truly simulate the morphology of the matrix.

[0006] Hydrogel fibers, as a new type of hydrogel material that has emerged in recent years, have attracted widespread attention and interest. Hydrogel fibers combine the advantages of fabrics and hydrogels and overcome the shortcomings of some traditional dressings. Hydrogel fibers have a high specific surface area and high air permeability, which helps to provide more effective gas exchange and reduce the moist environment and infection risk around the wound. Hydrogel fibers can maintain high water content and high elasticity, which helps to maintain the moisture balance on the surface of skin wounds, help soften and remove necrotic tissue, promote healing, and adapt to wounds of different shapes. At the same time, similar to hydrogel dressings, hydrogel fiber dressings are not easy to adhere to the wound, reducing pain and further damage during dressing changes. Therefore, by mimicking the complex structure and function of natural skin tissue, hydrogel fibers can promote wound healing, making them a new type of wound dressing suitable for skin regeneration.

[0007] There are many methods that can be used to prepare hydrogel fibers, including 3D bioprinting, electrospinning, fluid dynamic spinning, mechanical traction technology, etc. However, fluid dynamic spinning and electrospinning require specific process parameters (pressure, flow rate, electric field strength, etc.) that are difficult to control accurately; 3D bioprinting is limited by printing resolution and speed, resulting in poor performance of printed products; mechanical traction technology is not suitable for most hydrogel materials, especially those with low mechanical strength or fragile materials. Summary of the invention

[0008] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a degradable dry absorbent fabric based on pre-swelling.

[0009] The preparation process of the present invention is simple, the performance is controllable, and it is easy to process on a large scale; the dry absorbent fabric of the present invention can form a fibrous hydrogel with good liquid retention capacity, mechanical properties, and transparency after quickly absorbing liquid, and can be applied to various wound repair scenarios.

[0010] Another object of the present invention is to provide a degradable dry absorbent fabric prepared by the above method.

[0011] Another object of the present invention is to provide application of the above-mentioned degradable dry absorbent fabric in wound dressing materials.

[0012] The purpose of the present invention is achieved through the following solutions: A method for preparing a pre-swelling degradable dry absorbent fabric comprises the following steps: (1) soaking the base fabric in a pre-swelling solution, heating the base fabric to expand the structure of the sample, thereby exposing more fibers, washing, and rolling the base fabric to a water content of 30wt%-100wt%, to obtain sample a; (2) soaking sample a in an alkaline solution and reacting it under microwave assistance to obtain an alkaline sample b; (3) Adding chloroacetic acid solution to the alkalinized sample b for reaction, washing and drying the obtained etherification product to obtain a degradable dry absorbent fabric.

[0013] The base fabric in step (1) comprises, by mass percentage, 60%-100% cellulose fibers and 0%-40% non-cellulose fibers.

[0014] The cellulose fiber includes at least one of Tencel fiber, cotton fiber, viscose fiber, cuprammonium fiber, modal fiber, hemp fiber, and flax fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber.

[0015] The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, hem nonwoven fabric, knitted fabric, and woven fabric.

[0016] The solute of the pre-swelling solution in step (1) is at least one of a salt, an ionic liquid and a surfactant; and the solvent is water.

[0017] The anions of the salt are selected from at least one of chloride ion, bromide ion, iodide ion, sulfate ion, phosphate ion, hydrogen phosphate ion, and dihydrogen phosphate ion; the cations are selected from at least one of sodium ion, lithium ion, potassium ion, magnesium ion, zinc ion, and iron ion; and the amount of the salt used is 0%-100% of the water mass.

[0018] The ionic liquid is at least one of 1-butyl-3-methylimidazolium chloride, 1-butylpyridinium chloride, triethylhexyl ammonium chloride, and 1-butyl-3-methylimidazolium dimethyl phosphate; and the amount of the ionic liquid used is 50%-300% of the mass of water.

[0019] The HLB value of the surfactant is 12-20; the surfactant is selected from at least one of polyethylene glycol surfactants, polysorbate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, octylphenoxy polyethylene glycol, and fatty alcohol polyoxyethylene ether; the amount of the surfactant is 0%-5% of the water mass; wherein the polyethylene glycol surfactant includes at least one of PEG-20 stearate and PEG-40 hydrogenated castor oil; and the polysorbate includes at least one of Tween-20 and Tween-80.

[0020] In step (1), the mass ratio of the base fabric to the pre-swelling solution is 1:4-20.

[0021] The temperature of the heating treatment in step (1) is 40°C-70°C and the time is 0.5-2h.

[0022] The pressure of the rolling mill in step (1) is 0.1-1 MPa.

[0023] The alkaline solution in step (2) consists of a solute and water, wherein the mass ratio of the solute to water is 1-10:50.

[0024] The solute of the alkaline solution in step (2) is at least one of sodium bicarbonate, potassium bicarbonate, magnesium hydroxide, zinc hydroxide, lithium hydroxide, potassium hydroxide, sodium hydroxide, barium hydroxide, choline, ammonia, triethylamine, and piperidine.

[0025] The mass ratio of the alkaline solution in step (2) to the base fabric in step (1) is 4-20:1.

[0026] The power of the microwave in step (2) is 100-300 W; the temperature of the reaction is 30-60° C., and the reaction time is 2-10 min.

[0027] The mass ratio of chloroacetic acid to water in the chloroacetic acid solution of step (3) is 1-5:20.

[0028] The mass ratio of the chloroacetic acid solution in step (3) to the base fabric in step (1) is 4-20:1.

[0029] The reaction temperature in step (3) is 40-70°C and the reaction time is 0.2-2h.

[0030] The drying in step (3) is freeze-drying.

[0031] The degradable dry absorbent fabric is prepared by the method.

[0032] Application of the above-mentioned degradable dry absorbent fabric in wound dressing materials.

[0033] The application is specifically as follows: placing the degradable dry absorbent fabric in water to achieve water absorption equilibrium to obtain degradable hydrogel fibers; and using the degradable hydrogel fibers as wound dressings.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects: The fibers of the base fabric are expanded by treating with lithium bromide / water solution, which is convenient for subsequent treatment; microwave-assisted alkalization solves the problems of uneven alkalization of cellulose, high energy consumption, and long reaction time; etherification solves the problems of low water absorption and low liquid retention of cellulose base fabric. In addition, the preparation process of the present invention is simple, the performance is controllable, and it is easy to process on a large scale; the dry absorbent fabric of the present invention can form a fibrous hydrogel with good liquid retention capacity and transparency after quickly absorbing liquid, and can be applied to various wound repair scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1The present invention is a flow chart of a method for preparing a degradable dry absorbent fabric according to an embodiment of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] Unless otherwise specified, the reagents used in the examples can be purchased from the market.

[0038] The test method for the tensile properties of cellulose fabrics of the products obtained in Examples 1-10 and Comparative Examples 1-2 refers to Part 1: Determination of breaking strength and elongation at break (strip method) in GBT3923.1-2013 "Tensile Properties of Textile Fabrics".

[0039] Comparative Example 1 An untreated spunlaced nonwoven fabric (100 wt % cotton fiber) was used as a comparative example.

[0040] Performance Test: The dry cloth breaking strength of the product obtained in this example is 160 N; the water absorption rate is 7 times.

[0041] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing, and the breaking strength of the wet cloth was 80 N; it could retain water twice the mass of the dry cloth after centrifugation at 1000 rpm for 5 min; the skin-attachment time was 20 minutes; it was opaque; and it could be completely degraded after being cultured in a cellulase / PBS solution for 30 days.

[0042] Comparative Example 2 Step 1: 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) was soaked in 700 g of water at 50 °C for 40 min, and the moisture content of the sample was controlled to 50 wt% by a padder (pressure 0.5 MPa); Step 2, immersing the sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 3, adding 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and reacting at 55° C. for 30 minutes to obtain an etherified sample; Step 4: washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0043] Performance Test: The dry cloth breaking strength of the product obtained in this example is 100 N; the water absorption rate is 9 times.

[0044] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 55 N. After centrifugation at 1000 rpm for 5 min, it could retain 5 times the mass of the dry cloth in water. The skin adhesion time was 100 minutes. The transparency at 600 nm was 60%. It could be completely degraded after being cultured in a cellulase / PBS solution for 14 days.

[0045] Example 1 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0046] Performance Test: The dry cloth breaking strength of the product obtained in this example is 75 N; the water absorption rate is 15 times.

[0047] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 40 N. After centrifugation at 1000 rpm for 5 min, it could retain 9 times the mass of the dry cloth in water. The skin adhesion time was 160 minutes. The transparency at 600 nm was 93%. It could be completely degraded after being cultured in a cellulase / PBS solution for 7 days.

[0048] Example 2 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 1400 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 50 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0049] Performance Test: The dry cloth breaking strength of the product obtained in this example is 71 N; the water absorption rate is 20 times.

[0050] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 38 N. After centrifugation at 1000 rpm for 5 min, it could retain 12 times the mass of the dry cloth in water. The skin adhesion time was 180 minutes. The transparency at 600 nm was 96%. It could be completely degraded after being cultured in a cellulase / PBS solution for 5 days.

[0051] Example 3 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 40 °C for 80 minutes; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4, adding 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and reacting at 55° C. for 50 minutes to obtain an etherified sample; Step 5: Wash the sample with water and freeze-dry it to obtain the dry absorbent fabric.

[0052] Performance Test: The dry cloth breaking strength of the product obtained in this example is 80 N; the water absorption rate is 17 times.

[0053] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 41 N. After centrifugation at 1000 rpm for 5 min, it could retain 9 times the mass of the dry cloth in water. The skin adhesion time was 170 minutes. The transparency at 600 nm was 91%. It could be completely degraded after culturing in cellulase / PBS solution for 7 days.

[0054] Example 4 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:19, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:19) to the alkalized sample, and react at 55° C. for 50 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0055] Performance Test: The dry cloth breaking strength of the product obtained in this example is 90 N; the water absorption rate is 10 times.

[0056] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 47 N. After centrifugation at 1000 rpm for 5 min, it could retain 6 times the mass of the dry cloth in water. The skin adhesion time was 100 minutes. The transparency at 600 nm was 90%. It could be completely degraded after culturing in cellulase / PBS solution for 7 days.

[0057] Example 5 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated samples with water and control the water content of the samples to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4, adding 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and reacting at 65° C. for 20 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0058] Performance Test: The dry cloth breaking strength of the product obtained in this example is 80 N; the water absorption rate is 24 times.

[0059] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 38 N. After centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water. The skin adhesion time was 200 minutes. The transparency at 600 nm was 96%. It could be completely degraded after culturing in cellulase / PBS solution for 4 days.

[0060] Example 6 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated sample with water and control the sample to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 50°C with a microwave power of 200 W for 3 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0061] Performance Test: The dry cloth breaking strength of the product obtained in this example is 85 N; the water absorption rate is 13 times.

[0062] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 45 N. After centrifugation at 1000 rpm for 5 min, it could retain 5 times the mass of the dry cloth in water. The skin adhesion time was 100 minutes. The transparency at 600 nm was 90%. It could be completely degraded after culturing in cellulase / PBS solution for 7 days.

[0063] Example 7 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% Tencel fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated sample with water and control the sample to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0064] Performance Test: The dry cloth breaking strength of the product obtained in this example is 78 N; the water absorption rate is 17 times.

[0065] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 40 N. After centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water. The skin adhesion time was 180 minutes. The transparency at 600 nm was 95%. It could be completely degraded after culturing in cellulase / PBS solution for 7 days.

[0066] Example 8 Step 1: soak 100 g of spunlace nonwoven fabric (90 wt% viscose fiber + 10 wt% vinylon fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated sample with water and control the sample to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0067] Performance Test: The dry cloth breaking strength of the product obtained in this example is 85 N; the water absorption ratio is 21 times.

[0068] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 47 N. After centrifugation at 1000 rpm for 5 min, it could retain 10 times the mass of the dry cloth in water. The skin adhesion time was 200 minutes. The transparency at 600 nm was 91%. It could be completely degraded after culturing in cellulase / PBS solution for 6 days.

[0069] Example 9 Step 1: immerse 100 g of knitted fabric (100 wt% cotton fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated sample with water and control the sample to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0070] Performance Test: The dry cloth breaking strength of the product obtained in this example is 90 N; the water absorption rate is 26 times.

[0071] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 46 N. After centrifugation at 1000 rpm for 5 min, it could retain 11 times the mass of the dry cloth in water. The skin adhesion time was 210 minutes. The transparency at 600 nm was 92%. It could be completely degraded after culturing in cellulase / PBS solution for 6 days.

[0072] Example 10 Step 1: immerse 100 g of spunlace nonwoven fabric (100 wt% flax fiber) in 700 g of lithium bromide solution (the mass ratio of lithium bromide to water is 1:1) and treat at 50 °C for 40 minutes; Step 2: Wash the treated sample with water and control the sample to 50 wt% by rolling (pressure 0.5 MPa); Step 3, immersing the above sample in 1000 g of potassium hydroxide solution, wherein the mass ratio of potassium hydroxide to water is 1:9, and reacting at 40°C with a microwave power of 200 W for 5 minutes to obtain an alkaline sample; Step 4: add 500 g of chloroacetic acid solution (chloroacetic acid and water are mixed in a mass ratio of 1:9) to the alkalized sample, and react at 55° C. for 30 minutes to obtain an etherified sample; Step 5, washing the etherified sample with water and freeze-drying it to obtain the dry absorbent fabric.

[0073] Performance Test: The dry cloth breaking strength of the product obtained in this example is 90 N; the water absorption rate is 8 times.

[0074] After the product obtained in this example reached water absorption equilibrium in water, it was taken out for testing and the breaking strength of the wet cloth was 46 N. After centrifugation at 1000 rpm for 5 min, it could retain 8 times the mass of the dry cloth in water. The skin adhesion time was 170 minutes. The transparency at 600 nm was 93%. It could be completely degraded after culturing in cellulase / PBS solution for 6 days.

[0075] The test results of the finished products of the above embodiment show that: for a gram weight ≥ 35 g / m 2 According to the test method in GBT3923.1-2013 "Tensile Properties of Textile Fabrics", the dry absorbent fabrics (Examples 1-10) obtained after the treatment of the present invention have a dry cloth breaking strength of >70 N; and a wet cloth breaking strength of >35 N. Compared with the 7-fold water absorption rate of 100% cotton fiber spunlace non-woven fabric, the dry absorbent fabric obtained by the present invention can absorb 8-30 times of water; after centrifugation at 1000rpm for 5 minutes, it can still retain 5-13 times of water, and has good water retention capacity. After water absorption equilibrium, the dry absorbent fabric obtained by the present invention has a skin-attaching time extended by 7-9 times; the transparency at 600 nm is >90%, which is suitable for repairing skin wounds, and the healing of wounds can be observed without removing the dressing; it has good degradability and can be completely degraded after 7 days of culture in a cellulase / PBS solution.

[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a degradable dry absorbent fabric based on pre-swelling, characterized in that: The following steps are involved: (1) soaking the base fabric in a pre-swelling solution, heating the base fabric to expand the structure of the sample, thereby exposing more fibers, washing, and rolling the base fabric to a water content of 30wt%-100wt%, to obtain sample a; (2) soaking sample a in an alkaline solution and reacting it under microwave assistance to obtain an alkaline sample b; (3) Adding chloroacetic acid solution to the alkalinized sample b for reaction, washing and drying the obtained etherification product to obtain a degradable dry absorbent fabric.

2. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The base fabric in step (1) comprises, by mass percentage, 60%-100% cellulose fibers and 0%-40% non-cellulose fibers; The cellulose fiber includes at least one of tencel fiber, cotton fiber, viscose fiber, cuprammonium fiber, modal fiber, hemp fiber, and flax fiber; the non-cellulose fiber is an alkali-resistant non-cellulose fiber, including at least one of nylon fiber, vinylon fiber, and polypropylene fiber; The base fabric in step (1) is at least one of spunlace nonwoven fabric, needle-punched nonwoven fabric, hem nonwoven fabric, knitted fabric, and woven fabric.

3. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The solute of the pre-swelling solution in step (1) is at least one of a salt, an ionic liquid, and a surfactant; and the solvent is water.

4. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 3, characterized in that: The anion of the salt is selected from at least one of chloride ion, bromide ion, iodide ion, sulfate ion, phosphate ion, hydrogen phosphate ion, and dihydrogen phosphate ion; the cation is selected from at least one of sodium ion, lithium ion, potassium ion, magnesium ion, zinc ion, and iron ion; the amount of the salt is 0%-100% of the mass of water; The ionic liquid is at least one of 1-butyl-3-methylimidazolium chloride, 1-butylpyridinium chloride, triethylhexyl ammonium chloride, and 1-butyl-3-methylimidazolium dimethyl phosphate; the amount of the ionic liquid is 50%-300% of the mass of water; The HLB value of the surfactant is 12-20; the surfactant is selected from at least one of polyethylene glycol surfactants, polysorbate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, octylphenoxy polyethylene glycol, and fatty alcohol polyoxyethylene ether; the amount of the surfactant used is 0%-5% of the water mass.

5. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The mass ratio of the base fabric to the pre-swelling solution in step (1) is 1:4-20; The temperature of the heating treatment in step (1) is 40°C-70°C and the time is 0.5-2h; The pressure of the rolling mill in step (1) is 0.1-1 MPa.

6. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The alkaline solution in step (2) is composed of a solute and water, wherein the mass ratio of the solute to water is 1-10:50; The solute of the alkaline solution in step (2) is at least one of sodium bicarbonate, potassium bicarbonate, magnesium hydroxide, zinc hydroxide, lithium hydroxide, potassium hydroxide, sodium hydroxide, barium hydroxide, choline, ammonia, triethylamine, and piperidine.

7. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The mass ratio of the alkaline solution in step (2) to the base fabric in step (1) is 4-20:1; The power of the microwave in step (2) is 100-300 W; the temperature of the reaction is 30-60° C., and the reaction time is 2-10 min.

8. The method for preparing the pre-swelling degradable dry absorbent fabric according to claim 1, characterized in that: The mass ratio of chloroacetic acid to water in the chloroacetic acid solution of step (3) is 1-5:20; The mass ratio of the chloroacetic acid solution in step (3) to the base fabric in step (1) is 4-20:1; The reaction temperature in step (3) is 40-70°C and the reaction time is 0.2-2h.

9. The degradable dry absorbent fabric prepared by the method according to any one of claims 1 to 8.

10. Use of the degradable dry absorbent fabric according to claim 9 in wound dressing materials.

Citation Information

Patent Citations

  • Preparation method of skin-friendly composite fiber with high water absorbability

    CN117661325A